Causation in the law of the World Trade Organization : an econometric approach / Catherine Gascoigne. - Gascoigne, Catherine, 1983- (Cambridge international trade and economic law., 2023)
Written both for scholars and practitioners of WTO law with an interest in the causal questions that WTO law raises. The book discusses the problems in the current approach to causation in the WTO jurisprudence and proposes an alternative methodology that draws on causal philosophy and econometric analysis.